Changes in volume of stage I non-small-cell lung cancer during stereotactic body radiotherapy - Tatekawa, Kotoha (BioMed Central, 2014)
BACKGROUND: The overall treatment time of stereotactic body radiotherapy (SBRT) for non-small-cell lung cancer is usually 3 to over 10 days. If it is longer than 7 days, tumor volume expansion during SBRT may jeopardize the target dose coverage. In this study, volume change of stage I NSCLC during SBRT was investigated. METHODS: Fifty patients undergoing 4-fraction SBRT with a total dose of 48 Gy (n = 36) or 52 Gy (n = 14) were analyzed. CT was taken for registration at the first and third SBRT sessions with an interval of 7 days in all patients. Patient age was 29–87 years (median, 77), and 39 were men. Histology was adenocarcinoma in 28, squamous cell carcinoma in 17, and others in 5. According to the UICC 7th classification, T-stage was T1a in 9 patients, T1b in 27, and T2a in 14. Tumor volumes on the first and 8th days were determined on CT images taken during the exhalation phase, by importing the data into the Dr. View/LINAX image analysis system. After determining the optimal threshold for distinguishing tumor from pulmonary parenchyma, the region above -250 HU was automatically extracted and the tumor volumes were calculated. RESULTS: The median tumor volume was 7.3 ml (range, 0.5-35.7) on day 1 and 7.5 ml (range, 0.5-35.7) on day 8. Volume increase of over 10% was observed in 16 cases (32%); increases by >10 to ≤20%, >20 to ≤30%, and >30% were observed in 9, 5, and 2 cases, respectively. The increase in the estimated tumor diameter was over 2 mm in 3 cases and 1–2 mm in 6. A decrease of 10% or more was seen in 3 cases. Among the 16 tumors showing a volume increase of over 10%, T-stage was T1a in 2 patients, T1b in 9, and T2a in 5. Histology was adenocarcinoma in 10 patients, squamous cell carcinoma in 5, and others in 1. CONCLUSIONS: Volume expansion >10% was observed in 32% of the tumors during the first week of SBRT, possibly due to edema or sustained tumor progression. When planning SBRT, this phenomenon should be taken into account.